A proposed scheduling algorithm for real time application in 5G networks - Moaath Saleh Abdulrahman; Buthaina Mosa Omran (Universitas Ahmad Dahlan, 2025)
The third-generation partnership developed the fifth-generation specifications to satisfy the expansion of mobile applications and the grown demand for extra data flow. As the real time services in 5G networks are widespread, professional scheduling algorithms are necessary to deal with the assignment of the scarce frequency resources among different categories of applications, ensuring the quality of service and improving the user experience. This paper proposes a real time flow scheduling algorithm by enhancing the scheduling metric to prioritize real time flows such as voice and video, particularly as the packet delay approaches its threshold time. The performance metrics of the proposed algorithm were evaluated and compared to three well-known algorithms, which are the modified largest weighted delay first, the exponential proportional fair, and the logarithmic rule. The simulation results, which was conducted by a dedicated software, showed that the proposed algorithm achieved up to 1.5 times the throughput of the other algorithms and resulted in less than half the video packets loss ratio compared to others, moreover, it offered a higher fairness index between users than other algorithms for video packets.